МЕТОДЫ ФИТОТЕРАПИИ В ПРАКТИКЕ ВРАЧА-ОРТОДОНТА - Мухсинов Зафаржон Орифжонович, Холмуродов Бурхон Равшанович (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
Any method of treatment in medicine, and in particular orthodontic treatment, can cause the development of various complications. The presence in the mouth braces, rings, arcs, and ligatures significantly hampers the normal hygienic procedures, which creates conditions for the development of the periodontal inflammatory process (gingivitis, local and generalized periodontitis). Phytotherapy has been used in orthodontic practice for arrest of the inflammatory processes in the periodontium.